2013
DOI: 10.4081/ija.2013.e10
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and genetic components for pod and seed traits in cowpea lines

Abstract: The identification of suitable parental genotypes potentially generating superior lines with traits contributing to the overall yield of cowpea is an important step in the development of improved varieties. Eight parents and their 28 hybrids obtained through diallel crossing design were evaluated in a randomized complete block design with three replications. Highly significant differences among the parents and their hybrids for different traits were observed. General combining ability (GCA) mean squares were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
5
11
0
Order By: Relevance
“…Further results showed that none of the parents or specific cross was best for all the characters. Similar results were observed by others (Pandey andSingh, 2010 andAyo-Vaughan et al 2013).…”
Section: Combining Ability Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Further results showed that none of the parents or specific cross was best for all the characters. Similar results were observed by others (Pandey andSingh, 2010 andAyo-Vaughan et al 2013).…”
Section: Combining Ability Analysissupporting
confidence: 92%
“…In contrast, the characters with low narrow sense heritability and lower estimates of the dominance components compared with those of the additive (D), selection may be considerably difficult or virtually impractical due to the masking effect of environments on genotypic effects. Similar result was reported by Ayo-Vaughan et al (2013) in cowpea.…”
Section: Genetic Analysissupporting
confidence: 91%
“…The estimated variances due to specific combining ability were higher than general combining ability indicating the predominance of the nonadditive gene action in these traits in either or both environments. This report is also in agreement with Bhavesh Patel et al [23] and Selvarkumar et al [24], but in contrast to Ayo-Vaughan et al [25]. The estimates of predictability 8 Advances in Agriculture ratio less than unity in these traits suggest that performance of hybrids for these traits could be difficult to predict on the basis of general combining ability of parents due to the importance of dominance.…”
Section: Discussionsupporting
confidence: 73%
“…Significant GCA effect is a manifestation of additive and additive × additive gene interactions, which represents a heritable portion of genetic variation which is transmittable from the parent to its progeny [ 15 ]. This therefore could imply that early generation selection would be effective due to small environmental effects [ 16 , 30 ]. The significant negative GCA observed for IT86D-610 and Sanzi-Nya for days to 50% flowering and days to 90% pod maturity also suggests that these parents could contribute favorable alleles for breeding early maturity in cowpea.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies have been conducted on combining ability for grain yield and yield components in cowpea and other crops [ 16 19 ], few studies have been reported on combining ability and heritability of maturity traits and their relationship with grain yield in cowpea [ 16 ]. Early maturity relative to other crops is the unique attribute that makes cowpea one of the most important climate smart crops particularly in areas of short cropping seasons.…”
Section: Introductionmentioning
confidence: 99%